Pemanfaatan Tepung Daun Singkong sebagai Substitusi Tepung Terigu dalam Pembuatan Kukis [Utilization of Cassava Leaves Flour as Wheat Flour Substitute in the Making of Cookies] - Lucia Crysanthy Soedirga (Universitas Pelita Harapan, 2022)
Cookies are a product commonly made from wheat flour as the main ingredient and widely consumed by people. However, gluten in wheat flour can cause allergies, so the consumption of wheat-based products is limited. Furthermore, cookies also have low levels of protein and dietary fibre. Therefore, it is necessary to find another raw materials as an alternative in the making of cookies. In this research, wheat flour substituted with cassava leaves flour in various ratios (100:0; 90:10; 80:20; 70:30, and 60:40). The results showed that substituting wheat flour with cassava leaves flour at a ratio of 70:30 was the preferred ratio in making cookies. The resulting cookies have 10.24±0.11% of protein, 15.98±0.05 % of dietary fibre, 77.05 % of spread ratio, and 3512.47±126.68 g of hardness. In addition, the resulting cookies have slightly intense of cassava leaves aroma (4.88±1.17), slightly intense of cassava leaves taste (4.88 ±1.24), sandy (3.80±1.30) and hard (4.88±0.97) texture. The panellist slightly dislike the aroma (3.40±1.46) and taste (3.23±1.48). Meanwhile, the panellist slightly like the hardness of cookies (5.35±0.83). Further the panellist gave neutral acceptance on the sandy texture (4.75±1.54) and overall cookies (4.28±1.43). Bahasa Indonesia Abstract:Kukis merupakan salah satu jenis produk yang menggunakan tepung terigu sebagai bahan baku utama. Namun gluten pada tepung terigu dapat menyebabkan alergi sehingga konsumsi produk berbasis terigu menjadi terbatas. Selain itu kukis juga memiliki kadar protein dan serat pangan yang rendah, oleh sebab itu perlu dicari alternatif bahan baku utama dalam pembuatan kukis. Pada penelitian ini tepung terigu akan disubstitusi dengan tepung daun singkong pada berbagai rasio (100:0; 90:10; 80:20; 70:30, dan 60:40). Hasil menunjukkan bahwa substitusi tepung terigu dengan tepung daun singkong pada rasio 70:30 merupakan rasio terpilih dalam pembuatan kukis. Kukis yang dihasilkan memiliki memiliki 10,24±0,11 % protein, 15,98±0,05 % serat pangan, spread ratio 77,05 %, dan kekerasan 3512,47±126,68 g. Selain itu kukis pada rasio terpilih agak beraroma khas daun singkong (4,88±1,17), agak terasa daun singkong (4,88±1,24), memiliki tekstur berpasir (3,80±1,30) dan keras (4,88±0,97). Panelis agak tidak suka terhadap aroma (3,40±1,46) dan rasa 3,23±1,48). Namun, panelis agak menyukai tekstur kukis (5,35±0,83). Selain itu, panelis tingkat kesukaan netral diberikan panelis terhadap tekstur berpasir (4,75±1,54) dan penerimaan keseluruhan (4,28 ± 1,43).